2021
DOI: 10.1186/s12884-021-03656-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation for selective fetal reduction in complicated Monochorionic twins; comparing the outcomes according to the indications

Abstract: Background To evaluate the perinatal outcomes in women with complicated monochorionic diamniotic twins who underwent selective reduction using radiofrequency ablation (RFA). Methods This retrospective study included patients with complicated monochorionic diamniotic twins between 16 to 28 weeks who underwent selective reduction using RFA. Results During the study period, 143 women with complicated mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 19 publications
5
22
0
3
Order By: Relevance
“…Similarly, Rahimi-Sharbaf et al 35 recently reported the outcomes of RFA for selective fetal reduction in monochorionic twins based on indication with an overall survival of the co-twin following RFA as 71.3%. Wang et al 36 also report on how indications for 272 RFA procedures may affect the perinatal outcomes of monochorionic pregnancies.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, Rahimi-Sharbaf et al 35 recently reported the outcomes of RFA for selective fetal reduction in monochorionic twins based on indication with an overall survival of the co-twin following RFA as 71.3%. Wang et al 36 also report on how indications for 272 RFA procedures may affect the perinatal outcomes of monochorionic pregnancies.…”
Section: Resultsmentioning
confidence: 94%
“…Current literature, including studies by Kumar et al, 33 Lee et al, 17 Rahimi-Sharbaf et al, 35 Ting et al, 30 and Wang et al 36 evaluate outcomes following RFA but do not specifically compare elective RFA of monochorionic diamniotic twins to ongoing twin monochorionic diamniotic twin pregnancies. In order to determine perinatal outcomes following RFA in complex monochorionic pregnancies, Kumar et al 33 prospectively studied 100 cases of selective RFA of which 72 were monochorionic diamniotic twins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the treatment effect and perinatal outcomes 3 , 4 of radiofrequency ablation (RFA). However, little is known about the effect of the needle entry angle on perinatal outcomes 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The RFA needle is usually percutaneously inserted through the maternal abdominal wall into the intrauterine fetal abdomen at the level of the cord insertion site of the complicated twin. 4 6 However, the fetus sometimes maintains a prone position or suddenly changes position after the needle enters the uterine cavity. Whether this procedure should then be interrupted or a different needle insertion angle chosen remains unclear A fetal dorsal insertion angle may increase the complexity of the operation owing to factors, including spinal obstruction, more fetal tissue to pass through, and opposite directions between the umbrella end of the ablation needle and the umbilical artery and vein.…”
Section: Introductionmentioning
confidence: 99%